2016
DOI: 10.1111/acel.12463
|View full text |Cite
|
Sign up to set email alerts
|

Developing criteria for evaluation of geroprotectors as a key stage toward translation to the clinic

Abstract: SummaryIn the coming decades, a massive shift in the aging segment of the population will have major social and economic consequences around the world. One way to offset this increase is to expedite the development of geroprotectors, substances that slow aging, repair age‐associated damage and extend healthy lifespan, or healthspan. While over 200 geroprotectors are now reported in model organisms and some are in human use for specific disease indications, the path toward determining whether they affect aging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 94 publications
0
82
0
Order By: Relevance
“…This apparent paradox may reflect the existence of distinct networks of hypothalamic neurons governing consummatory and appetite behaviors [24,25] . Other studies showed that caloric restriction and physical exercise improved biomarkers of human aging such as body mass index, blood pressure, glucose, insulin, and lipids, and decreased the risk of aging-associated diseases such as diabetes and cardiovascular conditions [26] .…”
Section: Caloric Restriction Longevity and Circadian Rhythmsmentioning
confidence: 99%
See 2 more Smart Citations
“…This apparent paradox may reflect the existence of distinct networks of hypothalamic neurons governing consummatory and appetite behaviors [24,25] . Other studies showed that caloric restriction and physical exercise improved biomarkers of human aging such as body mass index, blood pressure, glucose, insulin, and lipids, and decreased the risk of aging-associated diseases such as diabetes and cardiovascular conditions [26] .…”
Section: Caloric Restriction Longevity and Circadian Rhythmsmentioning
confidence: 99%
“…While caloric restriction and physical exercise are the only known nonpharmacologic interventions capable of delaying aging in rodents and primates, efforts have recently been made to evaluate the relative merits of pharmacologic interventions using geroprotectors as a key stage toward clinical applications [26] . Despite limited clinical investigations performed thus far, the mTOR inhibitor RAD001 (everolimus) was reported to have beneficial effects on immunosenescence in elderly volunteers [26] .…”
Section: Caloric Restriction Longevity and Circadian Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological agents that decrease the rate of aging and extend lifespan are called geroprotectors [36][37][38]. The term «geroprotector» (literally «protecting from aging») was first coined by the Nobel Prize laureate Ilya Mechnikov, an outstanding Russian and French scientist, in 1910 [35], but those times the concept had not been widely used before enough empirical data was accumulated.…”
Section: % (M) [55]mentioning
confidence: 99%
“…Recently, the system of criteria for geroprotector identification and classification were proposed [37,38]. The main criteria are (1) the ability to prolong life, in addition, a potential geroprotector should (2) return the biomarkers of aging to the state characteristic of a young organism; (3) the dose providing effective use must be fundamentally lower than the toxic dose with (4) minimal side effects at therapeutic dosage, and, finally, (5) the quality of life in patients treating with geroprotectors should increase, and the physical, mental, emotional state should improve.…”
Section: % (M) [55]mentioning
confidence: 99%